Act of violence: Undecidability and embodiment in the Geochang civilian massacre. Issue 2 (October 2022) - Kang, Hye Yun
Mass killing during security practices is often conceptualized as either unintended consequences or state violence. Looking away from the conventional frame that focuses on intentions of perpetrators, I suggest focusing on the embodied act in perpetrating violence, which illuminates another mechanism that has not been fully explored in perpetrator studies. I argue that undecidability embedded in embodying national security prompts the act of violence. Drawing on performative theories of Derrida and Butler, I show how national security as the normative ideal is embodied through practices of security agents in a way in which the option of using violence appears as optimal, or even desirable, to achieve security. My theoretical argument is epitomized in the security practices that killed 517 civilians during the military operation in Geochang. By tracing the fifth operation order as a security script, I illuminate how civilian killing appears as a way of carrying out military orders. I first lay out my theoretical argument. Second, I introduce the script that prompts mass killing in the case of the Geochang civilian massacre and situate it within the contexts of the Korean War, the guerrilla war, and the Cold War. Finally, I analyze how security practices of the soldiers in Geochang generate mass violence.